2016
DOI: 10.1139/cjpp-2015-0131
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic ameliorative effects of sesame oil and alpha-lipoic acid against subacute diazinon toxicity in rats: hematological, biochemical, and antioxidant studies

Abstract: Diazinon (DZN) is a common organophosphorus insecticide extensively used for agriculture and veterinary purposes. DZN toxicity is not limited to insects; it also induces harmful effects in mammals and birds. Our experiment evaluated the protective and antioxidant potential of sesame oil (SO) and (or) alpha-lipoic acid (ALA) against DZN toxicity in male Wistar albino rats. DZN-treated animals exhibited macrocytic hypochromic anemia and significant increases in serum biochemical parameters related to liver injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(25 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“…Furthermore, cardiac injury caused by acute ischemic stroke could be attributed, at least in part, to oxidative stress. Similar increases in CK-MB, CK, and LDH levels have been attributed to oxidative stress by a number of studies [30, 31, 36]. A previous study showed that vitamin C (an antioxidant) decreased CK-MB, CK, and LDH levels in mice models of cardiotoxicity, supporting the oxidative stress hypothesis of cardiotoxicity [30].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Furthermore, cardiac injury caused by acute ischemic stroke could be attributed, at least in part, to oxidative stress. Similar increases in CK-MB, CK, and LDH levels have been attributed to oxidative stress by a number of studies [30, 31, 36]. A previous study showed that vitamin C (an antioxidant) decreased CK-MB, CK, and LDH levels in mice models of cardiotoxicity, supporting the oxidative stress hypothesis of cardiotoxicity [30].…”
Section: Discussionsupporting
confidence: 58%
“…The myocardial tissue showed histopathological changes that are characteristics of myocardial damage, as supported by higher CK-MB activity and CK and LDH levels in the serum of the rats of the 6h-ischemia group [30, 31]. MF and HF were depressed in ECG recording, but the MF/TF ratio remained unchanged after brain ischemia, suggesting that the balance of the autonomic nervous system was not altered.…”
Section: Discussionmentioning
confidence: 99%
“…SOD catalyzes the conversion of superoxide radical to hydrogen peroxide while CAT converts the later into water. These antioxidant enzymes can, therefore, alleviate the toxic effects of ROS Abdel-Daim et al, 2015). SOD and CAT activities were significantly reduced in rats treated with CPF, ABM, and their combination.…”
Section: Discussionmentioning
confidence: 95%
“…Also, our histopathological findings showed mild lesion in mixed treated groups as compared to TAAintoxicated group. The ability of ALA to ameliorate the TAA-induced elevation in serum liver enzymes, bilirubin, might be correlated to both its radical scavenging properties, indirect effect as a regulator of antioxidative systems (Abdel-Daim et al, 2015 andEl-Feki et al, 2016). The beneficial hypolipidemic effects of ALA were in accordance with the results obtained by Mythili et al (2006), who found that ALA supplementation was effective against cyclophosphamide-induced dyslipidemia.…”
Section: Discussionmentioning
confidence: 99%